PENEGAKAN HUKUM TERHADAP PELAKU PELANGGARAN LALU LINTAS - Dekie GG Kasenda (Jurnal Ilmu Hukum Tambun Bungai, 2017)
Law enforcement of traffic offenders is influenced by 5 factors, namely substance factor (law and regulation), law enforcement factors, facilities and infrastructure factors, especially budget to conduct raid, public awareness factor factor and society culture factor. These five factors are closely related, as they are central to law enforcement, and as a benchmark of the effectiveness of law enforcement. Of the five factors are its own law enforcement factors namely the police is the central point. This is due to the implementation carried out by law enforcers and law enforcement agencies from the police themselves also should be a role model by the wider community.